اولی الامرکے خصائص اسلامی تعلیمات کی روشنی میں تحقیقی مطالعہ: A research study in the light of Islamic teachings on the Qualities of authorities - Dr Umme Salma (Al Manhal Research Journal, 2023)
There are some kinds expected characteristics that an individual must possess to be able to Be come a successful Leader such as confidence, honest, polished, communication skills, empathy, optimism, enthusim, intuition, acting as a role model and so on. This article aims to discuss the principles and characteristics of responsible persons according to the Quran and teachings of The Holy Prophet ﷺ. Islam is a complete system of life, with basic guidance for all fields of life. Politics and governance of society. The teaching of The Holy Prophet Muhammadﷺ have complete instruction for each step of the formation of government, from selection to methodology to its expansion, and from constitutional and principles to practical details, It is necessary that national leadership must be Muslim, intellectually free from mental or physical disabilities and capable for performing governmental affairs in a manner able way, Among the distinguishing features of the national leader ship ,the leader must be honest person ,in this Article describe standards according to the Quran and sunnah for Leaders of Nation ,and provide a guideline for leadership which are mention in Islamic Sharia.